Neurodegeneration and Sport. Issue 6 (1st June 2015) - Davis, Gavin A.; Castellani, Rudolph J.; McCrory, Paul
Abstract: The recent interest in concussion in sport has resulted in significant media focus about chronic traumatic encephalopathy (CTE), although a direct causative link(s) between concussion and CTE is not established. Typically, sport-related CTE occurs in a retired athlete with or without a history of concussion(s) who presents with a constellation of cognitive, mood, and/or behavioral symptoms and who has postmortem findings of tau deposition within the brain. There are many confounding variables, however, that can account for brain tau deposition, including genetic mutations, drugs, normal aging, environmental factors, postmortem brain processing, and toxins. To understand the roles of such factors in neurodegenerative diseases that may occur in athletes, this article reviews some neurodegenerative diseases that may present with similar findings in nonathletes. The article also reviews pathological changes identified with normal aging, and reviews the pathological findings of CTE in light of all these factors. While many of these athletes have a history of exposure to head impacts as a part of contact sport, there is insufficient evidence to establish causation between sports concussion and CTE. It is likely that many of the cases with neuropathological findings represent the normal aging process, the effects of opiate abuse, or a variant of frontotemporal lobar degeneration. Whether particular genetic causes may place athletes at greater risk of neurodegenerative disease is yet to be determined.